The Effect of Working from Home on the Agglomeration Economies of Cities: Evidence from Advertised Wages - Liu, Sitian; Su, Yichen (The Review of Economics and Statistics, 2025)
Using job posting wage data, we find a substantial decrease in the urban wage premium for occupations with high working-from-home (WFH) adoption following the COVID-19 pandemic, accompanied by an employment shift away from large cities. Based on a conceptual framework, the empirical findings suggest that WFH adoption lowered the productivity premium of large cities. A skill-level decomposition reveals that the urban wage premium decline was largely driven by reduced wage returns to interpersonal skills in large cities, suggesting that the reduced urban productivity premium was a result of weakened agglomeration economies due to decreased interpersonal interactions in large cities.